The oldest false fairy wasp (Hymenoptera: Mymarommatidae) from Lower Cretaceous Lebanese amber - Álvarez-Parra, Sergio; Rasnitsyn, Alexandr P.; Azar, Dany (Zootaxa, 2024)
Mymarommatidae (Hymenoptera), also known as false fairy wasps, are mainly characterised by their minute size, the peculiar wings, and the bi-segmented petiole. They form part of the superfamily Mymarommatoidea together with the Cretaceous families †Alavarommatidae, †Dipterommatidae, and †Gallorommatidae. The clade Bipetiolarida embraces Mymarommatoidea and †Serphitoidea, the two proctotrupomorphan superfamilies whose members have bi-segmented petiole. The biology of the mymarommatids is poorly known and only one extant species is known to be an egg endoparasitoid of barklice (Psocodea). Here, we describe a new species of mymarommatid wasp, Archaeromma phoenicium sp. nov., from Lower Cretaceous (Barremian) amber of Lebanon. We compare it with the other species of the genus and discuss the validity of some characters for generic identification. This new species is the oldest representative of the genus Archaeromma Yoshimoto, 1975 and of the family Mymarommatidae. A checklist and a key to the species of Archaeromma is included. Furthermore, we discuss the palaeobiogeography of the Cretaceous mymarommatoids. The description of the new species increases the list of insect co-occurrences between Lebanese and Spanish ambers to 21 genera.